Big Book: An Attractive Way to Comprehend Reading Text for Young Learners - Rahmasari, Brigitta Septarini (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2022)
Introducing reading text from young learners should be supported by appropriate facilities and resources adequate infrastructure. Learning Reading should be managed in such a way as to create meaningful and enjoyable learning activities. The use of big book as a medium of learning is one of the efforts to understand the reading text for young learners. This research aims at knowing the application of Big Book in teaching student‟s reading comprehension of the second grade students of elementary school. The research design in this study is qualitative approach. The data are collected by using observation, interview, and documentation. Meanwhile, techniques of analzying data are data reduction, data display, and drawing conclusion. The subject of the research is the second grade students, which consists of 13 female and 7 male. The researcher is successful to use big book to teach reading comprehension. The students feel happy and interested when using big book. The researcher asks the students to read aloud the reading text individually and in a group, and then gives questions about the content of the text. Students are able to understand the reading text using big book. Based on the findings of research, the researcher also recommends conducting further research on using of Big Book.